The Canadian RNFA Odyssey - Blunt, Thomas; Radey, Jane; McKenzie, Robyn (Operating Room Nurses Association of Canada Journal, 2001)
The Registered Nurse First Assistant (RNFA) is an experienced perioperative nurse with additional education and skills, functioning at an advanced level of nursing practice. The RNFA is a unique position that may encompass all areas of perioperative patient care, (preoperative, intraoperative and postoperative).